Cognitive restructuring effects on cognitive distortions in adolescents in grief over parent’s death (Boletin Médico de Postgrado, 2020)
The goal of this study is to evaluate the effects of cognitive restructuring on cognitive distortions in adolescents in grief over their parent’s death. A descriptive, cross-sectional, with quasi-experimental design was performed on 10 high school students of public and private institutions who lost one or both parents. An instrument of closed questions was designed with a reliability of 0.94. The results show that 35% of adolescents had cognitive distortions before the study (emotional reasoning, overgeneralization, dichotomous thinking and personalization); after therapy 25% persisted with these distortions. Regarding the dimension stimuli, 63% were affected by conversations about their deceased parents; after therapy, only 25% were still affected. Sadness and anger was detected in 63% of adolescents; after the application of the technique, these emotional expressions presented only in 48% of participants. The analysis of the data revealed the effectiveness of this technique to modify cognitive distortions in this group of adolescents.
Keywords: cognitive restructuring; cognitive distortions; grief; adolescents